Large Displacements in Tire Inflation Problem - Pelc, J. (Engineering Transactions, 1992)
In the paper a method for pneumatic tire structural analysis is described, taking into account large displacements and cord-rubber plies material properties. Axisymmetrical state of deformation is considered. The developed numerical algorithms and computer codes are verified by solving same benchmark problems. Simplified radial truck tire model is used for this purpose. The results were found to be in good agreement with other available data.